Genomic factors involved in neurodevelopment disorders - Angélica María Forero Ladino; Lina Johanna Moreno Giraldo (Universidad Libre, 2021)
I Background: Intellectual disability is part of the neurodevelopmental disorders, affecting 1-3 % of the population. The etiology is multifactorial, being genetic factors an important aspect in the disturbance of adaptative and intellectual skills, their heterogeneous presentation makes clinical and genetic diagnosis more difficult. With the advent of genomic techniques, it has been possible to detect and correlate possible candidate genes that cause these alterations, however, there are genetic variants that are difficult to interpret. Methods: Through this review it implemented a phenotype / genotype approach with a bioinformatic study, in order to be able to perform the reclassification of clinical significance of such variants according to the recommendation of the American College of Genetics and Genomics (ACMG) and to determine the true clinical of these genomic variants.  This in order to establish an early and timely diagnosis, an specific and directed treatment, an adequate follow up and prognosis and finally to offer an appropriate genetic counseling to the patient and his family group. Results: The early identification of genomic variations, through software and databases, allows establishing an opportune diagnosis that leads to early treatment, follow-up, prognosis and genetic counseling.